Lean Manufacturing Improves Emergency Department Throughput and Patient Satisfaction. (September 2015) - Kane, Marlena; Chui, Kristen; Rimicci, Janet; Callagy, Patrice; Hereford, James; Shen, Sam; Norris, Robert; Pickham, David
Abstract : A multidisciplinary team led by nursing leadership and physicians developed a plan to meet increasing demand and improve the patient experience in the ED without expanding the department's current resources. The approach included Lean tools and engaged frontline staff and physicians. Applying Lean management principles resulted in quicker service, improved patient satisfaction, increased capacity, and reduced resource utilization. Incorporating continuous daily management is necessary for sustainment of continuous improvement activities.